Polypharmacology modelling using proteochemometrics (PCM): recent methodological developments, applications to target families, and future prospects. Issue 1 (27th October 2014) - Cortés-Ciriano, Isidro; Ain, Qurrat Ul; Subramanian, Vigneshwari; Lenselink, Eelke B.; Méndez-Lucio, Oscar; IJzerman, Adriaan P.; Wohlfahrt, Gerd; Prusis, Peteris; Malliavin, Thérèse E.; van Westen, Gerard J. P.; Bender, Andreas
Abstract : Proteochemometric (PCM) modelling is a computational method to model the bioactivity of multiple ligands against multiple related protein targets simultaneously. Abstract : Proteochemometric (PCM) modelling is a computational method to model the bioactivity of multiple ligands against multiple related protein targets simultaneously. Hence it has been found to be particularly useful when exploring the selectivity and promiscuity of ligands on different proteins. In this review, we will firstly provide a brief introduction to the main concepts of PCM for readers new to the field. The next part focuses on recent technical advances, including the application of support vector machines (SVMs) using different kernel functions, random forests, Gaussian processes and collaborative filtering. The subsequent section will then describe some novel practical applications of PCM in the medicinal chemistry field, including studies on GPCRs, kinases, viral proteins ( e.g. from HIV) and epigenetic targets such as histone deacetylases. Finally, we will conclude by summarizing novel developments in PCM, which we expect to gain further importance in the future. These developments include adding three-dimensional protein target information, application of PCM to the prediction of binding energies, and application of the concept in the fields of pharmacogenomics and toxicogenomics. This review is an update to a related publication in 2011 and it mainly focuses on developments in the field since then.